Chenodeoxycholic acid stimulates glucagon‐like peptide‐1 secretion in patients after Roux‐en‐Y gastric bypass. Issue 3 (15th February 2017) - Nielsen, Signe; Svane, Maria S.; Kuhre, Rune E.; Clausen, Trine R.; Kristiansen, Viggo B.; Rehfeld, Jens F.; Holst, Jens J.; Madsbad, Sten; Bojsen‐Moller, Kirstine N.
Abstract: Postprandial secretion of glucagon‐like peptide‐1 (GLP‐1) is enhanced after Roux‐en‐Y gastric bypass (RYGB), but the precise molecular mechanisms explaining this remain poorly understood. Plasma concentrations of bile acids (BAs) increase after RYGB, and BAs may act as molecular enhancers of GLP‐1 secretion through activation of TGR5‐receptors. We aimed to evaluate GLP‐1 secretion after oral administration of the primary bile acid chenodeoxycholic acid (CDCA) and the secondary bile acid ursodeoxycholic acid (UDCA) (which are available for oral use) in RYGB‐operated participants. Eleven participants (BMI 29.1 ± 1.2, age 37.0 ± 3.2 years, time from RYGB 32.3 ± 1.1 months, weight loss after RYGB 37.0 ± 3.1 kg) were studied in a placebo‐controlled, crossover‐study. On three different days, participants ingested (1) placebo (water), (2) UDCA 750 mg, (3) CDCA 1250 mg (highest recommended doses). Oral intake of CDCA increased plasma concentrations of GLP‐1, C‐peptide, glucagon, peptide YY, neurotensin, total bile acids, and fibroblast growth factor 19 significantly compared with placebo (all P  < 0.05 for peak and positive incremental area‐under‐the‐curve (piAUC)). All plasma hormone concentrations were unaffected by UDCA. Neither UDCA nor CDCA changed glucose, cholecystokinin or glucose‐dependent insulinotropic polypeptide (GIP) concentrations. In conclusion, our findings demonstrate that the primary bile acid chenodeoxycholic acid is able to enhance secretion of gut hormones when administered orally in RYGB‐operated patients—even in the absence of nutrients. Abstract : Postprandial secretion of glucagon‐like peptide‐1 (GLP‐1) is enhanced after Roux‐en‐Y gastric bypass (RYGB), but the precise molecular mechanisms explaining this remain poorly understood. We aimed to evaluate GLP‐1 secretion after oral administration of the primary bile acid chenodeoxycholic acid (CDCA) and the secondary bile acid ursodeoxycholic acid (UDCA) in 11 participants 32.3 ± 1.1 months after uncomplicated RYGB. We found that CDCA, but not UDCA, stimulated GLP‐1, PYY, neurotensin, C‐peptide and glucagon secretion.